Mechanical behavior of PCL Nano fibers - (:unkn) unknown (Trans Tech Publications Ltd, 2016)
The biomedical applications of Poly (e-caprolactone) (PCL) have an extensive usage area such as tissue engineering, regenerative medicine, cartilage defects and biomedical implants. Because of the PCL's high biocompatibility and excellent mechanical features some implants have been designed for getting remarkable results. Clinically approved fibers ranging from 500 nm to 750 nm were produced by electrospinning method. The mechanical properties of the fiber scaffolds were performed via tensile testing and results were measured by special programme. Five different fiber scaffolds which they produced in various compositions have been used for this research. © 2016 Trans Tech Publications, Switzerland.
Keywords: Biopolymers; Electrospinning; Mechanical Testing; PCL